FOXP3 expression in blood, synovial fluid and synovial tissue during inflammatory arthritis and intra-articular corticosteroid treatment. Issue 12 (9th December 2008) - Raghavan, S; Cao, D; Widhe, M; Roth, K; Herrath, J; Engström, M; Roncador, G; Banham, A H; Trollmo, C; Catrina, A I; Malmström, V
Abstract : Objective: To analyse the distribution of FOXP3+CD25+CD4+ regulatory T cells (Treg) in peripheral blood, synovial fluid and tissue of patients with rheumatic disease during relapse and after local treatment. Methods: FOXP3 expression was assessed by flow cytometry, immunohistochemistry, immunofluorescence and real-time polymerase chain reaction (RT-PCR). The functional suppressive capacity of Treg was analysed after co-culture with effector CD4+CD25− T cells through assessment of proliferation and cytokine secretion. Results: It was shown that FOXP3 protein and mRNA expression in synovial fluid T cells was not confined solely to CD25 bright T cells as seen in blood, but included CD25 intermediate and even CD25 neg T cells. Indeed, synovial fluid CD25 high T cells showed similar suppressive capacity as CD25 bright T cells, indicating the presence of functional Treg in T cells with lower intensity of CD25. In synovial tissue, FOXP3+ cells were present in low numbers within T-cell infiltrates and decreased further after intra-articular glucocorticosteroid administration, in parallel with the general reduction in inflammation. Conclusions: Identification of synovial fluid FOXP3+ Treg with varying intensities of CD25 opens up possibilities for thorough characterisation of this important T-cell subset in the inflammatory compartment. However, only scarce synovial membrane expression of FOXP3 was found even in the absence of overt inflammation, suggesting that the synovial membrane is a site that would benefit therapeutically from Treg expansion.